Monsoon source shifts during the drying mid-Holocene: Biomarker isotope based evidence from the core 'monsoon zone' (CMZ) of India. (1st September 2015) - Sarkar, Saswati; Prasad, Sushma; Wilkes, Heinz; Riedel, Nils; Stebich, Martina; Basavaiah, Nathani; Sachse, Dirk
Abstract: A better understanding of past variations of the Indian Summer Monsoon (ISM), that plays a vital role for the still largely agro-based economy in India, can lead to a better assessment of its potential impact under global climate change scenarios. However, our knowledge of spatiotemporal patterns of ISM strength is limited due to the lack of high-resolution, continental paleohydrological records. Here, we reconstruct centennial-scale hydrological variability during the Holocene associated to changes in the intensity of the ISM based on a record of lipid biomarker abundances and compound-specific stable isotopic composition of a 10 m long sediment core from saline–alkaline Lonar Lake, situated in the core 'monsoon zone' of central India. We identified three main periods of distinct hydrology during the Holocene in central India. The period between 10.1 and 6 cal ka BP was likely the wettest during the Holocene. Lower average chain length (ACL) index values (29.4–28.6) and negative δ 13 Cwax values (−34.8‰ to −27.8‰) of leaf wax n -alkanes indicate the dominance of woody C3 vegetation in the catchment, and negative δDwax values (concentration weighted average) (−171‰ to −147‰) suggest a wet period due to an intensified monsoon. After 6 cal ka BP, a gradual shift to less negative δ 13 Cwax values (particularly for the grass derived n -C31 ) and appearance of the triterpene lipid tetrahymanol, generally considered as a marker for salinity and water column stratification, mark the onset of drier conditions. At 5.1 cal ka BP an increasing flux of leaf wax n -alkanes along with the highest flux of tetrahymanol indicate a major lowering of the lake level. Between 4.8 and 4 cal ka BP, we find evidence for a transition to arid conditions, indicated by high and strongly variable tetrahymanol flux. In addition, a pronounced shift to less negative δ 13 Cwax values, in particular for n -C31 (−25.2‰ to −22.8‰), during this period indicates a change of dominant vegetation to C4 grasses. In agreement with other proxy data, such as deposition of evaporite minerals, we interpret this period to reflect the driest conditions in the region during the last 10.1 ka. This transition led to protracted late Holocene arid conditions after 4 ka with the presence of a permanent saline lake, supported by the sustained presence of tetrahymanol and more positive average δDwax values (−122‰ to −141‰). A late Holocene peak of cyanobacterial biomarker input at 1.3 cal ka BP might represent an event of lake eutrophication, possibly due to human impact and the onset of cattle/livestock farming in the catchment. A unique feature of our record is the presence of a distinct transitional period between 4.8 and 4 cal ka BP, which was characterized by some of the most negative δDwax values during the Holocene (up to −180‰), when all other proxy data indicate the driest conditions during the Holocene. These negative δDwax values can as such most reasonably be explained by a shift in moisture source area and/or pathways or rainfall seasonality during this transitional period. We hypothesize that orbital induced weakening of the summer solar insolation and associated reorganization of the general atmospheric circulation, as a possible southward displacement of the tropical rainbelt, led to an unstable hydroclimate in central India between 4.8 and 4 ka. Our findings shed light onto the sequence of changes during mean state changes of the monsoonal system, once an insolation driven threshold has been passed, and show that small changes in solar insolation can be associated with major hydroclimate changes on the continents, a scenario that may be relevant with respect to future changes in the ISM system. Highlights: We analyzed biomarkers, their stable isotopes (C, H) from Lonar Lake record, India. We identified 3 hydrological periods over the Holocene in the core 'monsoon zone'. We found unstable hydrology in the transition of wet early and dry late Holocene. We suggest a weaker monsoon and a shift in its moisture sources/seasonality. We suggest circulation change due to threshold in radiative forcing from insolation.